2019
DOI: 10.3390/v11090813
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Dependent Porcine Circovirus Type 2 (PCV2) Entry and Replication in T-Lymphoblasts

Abstract: Porcine circovirus type 2 (PCV2) is the etiological agent of PCV2-associated diseases (PCVAD). PCV2 targets lymphoblasts, and pigs suffering from PCVAD display lymphocyte depletion in lymphoid tissues. PCV2 infection of lymphoblasts has not been studied. Here, the replication cycle of PCV2 (abortion strain 1121 and PMWS strain Stoon1010) in T-lymphoblasts was examined. The expression of Rep and Cap were found for both viral strains, while progeny virus was detected for Stoon1010 but not for 1121. PCV2 attached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 70 publications
0
26
0
Order By: Relevance
“…PCV2 is a naked circular single stranded DNA virus belonging to the Circoviridae family and responsible for Porcine CircoVirus Disease (PCVD). The attachment of PCV2 to target cells occurs through chondroitin sulfate B and probably other receptors [32]. Internalisation is not fully known but it does not seem to involve a specific receptor and the GAGs could mediate internalisation and binding to the target cells [33].…”
Section: Porcine Circovirus Typementioning
confidence: 99%
“…PCV2 is a naked circular single stranded DNA virus belonging to the Circoviridae family and responsible for Porcine CircoVirus Disease (PCVD). The attachment of PCV2 to target cells occurs through chondroitin sulfate B and probably other receptors [32]. Internalisation is not fully known but it does not seem to involve a specific receptor and the GAGs could mediate internalisation and binding to the target cells [33].…”
Section: Porcine Circovirus Typementioning
confidence: 99%
“…PCV-2 attachment to the cell surface is mediated by glycosaminoglycans (GAGs) heparan sulfate (HS) and chondroitin sulfate B (CSB) [30], which might be less variable between hosts than other cell receptors. Additionally, previous research has revealed that PCV-2 could still infect mutant hamster ovary (CHO) cells that did not express GAGs, indicating that other yet unidentified cellular surface molecules contribute to PCV-2 binding to the host cell [31]. Therefore, despite not being fully understood, the PCV-2 infection mechanism could favor entrance into different host cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…As reported, PCV2 can infect and replicate in epithelial, monocytic, and endothelial cells and fibrocytes, including intestinal porcine epithelial cell line (IPEC-J2) and porcine alveolar macrophage (PAM) [ 35 , 36 , 37 , 38 , 39 ]. In addition, PCV3 has been detected in almost all tissues and fluids, including the brain, kidney, heart, spleen, serum, pleural effusion, peritoneal cavity fluid, oral and nasal fluids, feces, and semen collected from the sick piglets and/or healthy animals [ 8 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Genome Protein and Lifecycle Of Pcvmentioning
confidence: 99%
“…The life cycle of PCV is mainly based on PCV1 and PCV2, while PCV3 and PCV4 were discovered later, so there is relatively little knowledge about their life cycles. During infection ( Figure 2 ), PCV2 interacts with heparin sulfate (HS) and/or chondroitin sulfate B glycosaminoglycan in an asymmetric mode to attach to host cells, which depends on arginine, lysine, and polar amino acids of Cap [ 39 , 45 , 46 , 47 ]. The interaction between virion and heparin is reversible, which depends on the size of heparin and is mainly determined by sulfates [ 46 , 47 ].…”
Section: Genome Protein and Lifecycle Of Pcvmentioning
confidence: 99%